The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1364/ol.419093
|View full text |Cite
|
Sign up to set email alerts
|

Origami-based microwave absorber with a reconfigurable bandwidth

Abstract: Reconfigurability is critical for the research fields in electromagnetics, mechanics, and acoustics, due to the controllability of functionalities. This Letter numerically and experimentally demonstrates an origami-based absorber with a reconfigurable bandwidth. The proposed structure provides four transformable models: flat sheet, single-arch-folded, double-arch-folded, and U-shaped strips filled, corresponding to the performance of nearly no absorption, one-peak absorption, two-peak absorption, and ultra-bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…With the shape transformation (i.e., origami or kirigami), the EM properties of the MAs can be tailored effectively and directly. [39,[97][98][99][100][101] Due to the emerging unique tuning mechanism as well as simple fabrication, the structural transformation-based technique has been a topic of great interest in tunable/reconfigurable MAs.…”
Section: Tuning Theory and Approaches In Masmentioning
confidence: 99%
See 2 more Smart Citations
“…With the shape transformation (i.e., origami or kirigami), the EM properties of the MAs can be tailored effectively and directly. [39,[97][98][99][100][101] Due to the emerging unique tuning mechanism as well as simple fabrication, the structural transformation-based technique has been a topic of great interest in tunable/reconfigurable MAs.…”
Section: Tuning Theory and Approaches In Masmentioning
confidence: 99%
“…Instead of using metallic resonators, Chen et al demonstrated an origami-based MA, which had been achieved through 3D printing of lossy conductive poly(lactic acid) (PLA). [39] The printed PLA sheet could be folded to transform different shapes, providing four models including flat sheet, single-arch-folded, double-arch-folded, and U-shaped strips. As a result, multifunctional microwave absorbers were obtained to offer switchable performance from nearly zero absorption to near-unity, dual-band, and ultra-broadband [96] Copyright 2018, The Authors, published by Hindawi.…”
Section: Structural Transformation For Tunable/ Reconfigurable Masmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [ 29 ] present an inkjet-printed PET substrate-based broadband MMA (1.0–4.5 GHz). An origami-based microwave absorber is presented in [ 30 ] for reconfigurable absorption bandwidth from 3.4 to 18 GHz frequency. Besides the triple absorption band, MMAs are offered in [ 31 , 32 , 33 , 34 , 35 ] with various patch designs.…”
Section: Introductionmentioning
confidence: 99%
“…The unitary structure of the MDM absorber, also known as a meta-atom, primarily has a regular and simple geometry, including squares, 16 rectangles, 17 crosses 18 and circles. 19 So far, the studies on these absorbers have extended to various wavelength bands, such as microwave, 20,21 terahertz, [22][23][24][25] long-wave infrared, 26 mid-wave infrared 27 and visible-nearinfrared bands. 28 It is worth mentioning that Karmakar et al 25 designed a metamaterial refractive index sensor by making use of the tuning effect of Fano resonance in the THz band in a geometrically symmetric stacked metamaterial.…”
Section: Introductionmentioning
confidence: 99%